An implementation program targeted at non-physician, anaesthesia assistants improves the quality of laryngeal mask anaesthesia. Issue 2 (20th November 2013) - Reed, Isabelle; Walker, Ellie; Oliver Rose, Bernd
Abstract: The laryngeal mask airway (LMA) is used to facilitate adequate ventilation in the majority of procedures requiring general anaesthesia in the UK. Excessive LMA cuff pressure and/or volume, generated by injection of air to form an adequate seal within the upper airway, has been associated with pharyngolaryngeal morbidity, an indicator of quality in anaesthetic practice. However, measurement of LMA cuff pressure to limit excessive cuff pressure is not routine practice, despite trial data showing this reduces adverse outcomes. Our aim was to reduce morbidity from the LMA through the implementation of an educational and interventional program targeted at anaesthetic nurses and operating department assistants (ODA), to alter their physician colleagues' practice. LMA cuff pressure measurements were made, and postoperative outcomes recorded, in an observational cohort of surgical patients over an initial 2-month period. These results, including patient morbidity and the evidence for LMA cuff pressure measurement, were presented to anaesthesia providers and their assistants. An implementation plan to adjust pressures within recommended levels was then undertaken by anaesthesia assistants. In 90 patients, >95% of LMA pressures were beyond the recommended level; higher volumes of injected air correlated with excess pressure (r=0.58; p<0.0001) and were associated with pharyngolaryngeal morbidity in 28% patients (P=0.04). There was no association with difficulty in LMA insertion, duration or type of surgical procedure. In the implementation cohort (102 patients), pharyngolaryngeal morbidity was reduced to 11% (P=0.001) in the 45 patients where LMA cuff pressure was reduced to within normal limits (absolute risk reduction: 38% (95% CI: 22-54%). LMA manometry in three patients (95% CI: 2-5) was required to prevent an episode of postoperative pharyngolaryngeal morbidity. A systematic educational and interventional program targeted at the entire perioperative anaesthesia team, but implemented by anaesthesia assistants, can improve perioperative safety and quality.